Vertisols of Ghana: Uses and potential for improved management using cattle - Cobbina, J. (International Livestock Centre for Africa, 1988)
Describes soil characteristics, uses, management, and productivity of vertisols in Ghana and discusses the potential for improved management using draught oxen. Includes recommendations.